Acceleration of vegetation dynamics in hydrologically connected wetlands caused by dam operation. Issue 2 (10th January 2021) - Zheng, Lilin; Xu, Jinying; Wang, Dandan; Xu, Guoyu; Tan, Zhiqiang; Xu, Ligang; Wang, Xiaolong
Abstract: The dynamic responses of wetlands to upstream water conservancy projects are becoming increasingly crucial for watershed management. Poyang Lake is a dynamic wetland system of critical ecological importance and connected with the Yangtze river. However, in the context of disturbed water regime in Poyang Lake resulting from human activities and climate change, the responses of vegetation dynamics to the Three Gorges Dam (TGD) have not been investigated. We addressed this knowledge gap by using daily water level data and Landsat images from 1987 to 2018. Landsat images were acquired between October and December to ensure similar phenological conditions. Object‐oriented Artificial Neural Network Regression for wetland classification was developed based on abundant training and validation samples. Interactions between vegetation coverage and water regimes pre and post the operation of the TGD were compared using classification and regression trees and the random forest model. Since the implementation of the TGD in 2003, Poyang Lake has become drier, especially during the dry season. A more rapid plant growth rate was observed post TGD (44.74 km 2 year −1 ) compared to that of the entire study period (12.9 km 2 year −1 ). Average water level for the antecedent 20 days most significantly affected vegetation before 2003, whereas average water level for the antecedent 5 or 10 days was more important after 2003. The impoundment of the TGD after the flood season accelerated the drawdown processes of Poyang Lake, and the rapidly exposed wetlands accelerated vegetation expansion during the dry seasons, resulting in shrinkage and degradation of the lake area. This study deepens our knowledge of the influences of newly developed dams on lakes and rivers. Abstract : Drawdown processes of Poyang Lake level during dry season were quickened post the operation of Three Gorges Dam (TGD). Antecedent near‐term water level fluctuations exerted strong influences on vegetation coverage. Quickened drawdown processes of Poyang Lake accelerated vegetation expansion.